THE INFLUENCE OF GENETIC POLYMORPHISMS ON THE TOXICITY OF PLATINUM-BASED CHEMOTHERAPY IN THE TREATMENT OF NON-SMALL CELL LUNG CANCER - Spasic, Jelena; Radosavljević, Davorin; Nagorni Obradović, Ljudmila (Medicinski podmladak, 2021)
Lung cancer remains one of the most frequent and the deadliest of malignant diseases throughout the world. Target and immune therapy have revolutionalised the treatment of this disease, but platinum-based chemotherapy still has a place in the treatment algorithm. The toxicity profile of cisplatin is well known and can be a limiting factor in the adequate treatment delivery of the drug. There are important interindividual differences in the efficacy and the toxicity of all chemotherapy drugs, which cannot be explained solely by the characteristics of the tumor. In order to define predictive factors for the occurrence of toxic effects, many genetic alterations have been investigated, especially single nucleotide polymorphisms (SNPs). Genes investigated are those involved in DNA repair mechanisms, signal pathways of apoptosis, DNA synthesis, transport mechanisms, but often with inconclusive and opposing results. It is clear that the effect of SNPs on the occurrence of cisplatin toxicity cannot be explained by investigating just one or several genes alone, but epigenetic interactions must be investigated, as well as interactions with outside factors. The study of SNPs is, however, a relatively simple and inexpensive method and as such can be used as one of the prognostic tools for everyday practice.